Predicting Body Image Satisfaction in Adolescents with Physical Disabilities: The Role of Frustration Tolerance and Social Competence - Lee, Angel; Maisarah, Syarifah (Psychological Research in Individuals with Exceptional Needs, 2025)
This study aimed to examine the predictive role of frustration tolerance and social competence in body image satisfaction among adolescents with physical disabilities. This research utilized a correlational descriptive design with a sample of 350 adolescents with physical disabilities, selected based on Morgan and Krejcie’s sample size determination table. Participants completed standardized self-report measures assessing body image satisfaction (MBSRQ), frustration tolerance (FDS), and social competence (SSRS). Data analysis was conducted using Pearson correlation to explore associations between variables and linear regression to determine the predictive power of frustration tolerance and social competence on body image satisfaction. All statistical analyses were performed using SPSS-27, and assumptions of normality, linearity, and multicollinearity were confirmed before conducting the regression analysis. Descriptive statistics showed that participants had a mean body image satisfaction score of 74.56 (SD = 9.87), a frustration tolerance score of 62.34 (SD = 8.23), and a social competence score of 68.21 (SD = 7.95). Correlation analysis revealed significant positive relationships between body image satisfaction and frustration tolerance (r = 0.52, p < 0.01) and body image satisfaction and social competence (r = 0.61, p < 0.01). The regression model was statistically significant (F(2, 347) = 90.75, p < 0.01, R² = 0.46), indicating that frustration tolerance (B = 0.42, β = 0.39, t = 5.25, p < 0.01) and social competence (B = 0.56, β = 0.47, t = 7.91, p < 0.01) were both significant predictors of body image satisfaction. The findings suggest that higher frustration tolerance and greater social competence are associated with increased body image satisfaction in adolescents with physical disabilities, with social competence playing a slightly stronger role. These results highlight the importance of resilience-building and social skills interventions to enhance body image satisfaction in this population.